Radiometric temperature measurements - Zhang, Zhuomin M.; Tsai, Benjamin K.; Machin, Graham (Academic Press, 2009)
This book describes the theory of radiation thermometry, both at a primary level and for a variety of applications, such as in the materials processing industries and remote sensing. This book is written for those who will apply radiation thermometry in industrial practice; use radiation thermometers for scientific research; the radiation thermometry specialist in a national measurement institute; developers of radiation thermometers who are working to innovate products for instrument manufacturers, and developers of non-contact thermometry methods to address challenging thermometry problems. The authors of each chapter were chosen from a group of international scientists who are experts in the field and specialists on the subject matter covered in the chapter. A large number of references are included at the end of each chapter as a resource for those seeking a deeper or more detailed understanding. This book is more than a practice guide, readers will gain in-depth knowledge in: (1) the proper selection of the type of thermometer; (2) the best practice in using the radiation thermometers; (3) awareness of the error sources and subsequent appropriate procedure to reduce the overall uncertainty; and (4) understanding of the calibration chain and its current limitations. Covers all fundamental aspects of the radiometric measurements Discusses practical applications with details on the instrumentation, calibration, and error sources Authorsare from leading national labs working in R & D of temperature measurements.